Handbook of research on entrepreneurship, innovation, sustainability, and ICTs in the post-COVID-19 era - Carvalho, Luísa Cagica, 1970-; Reis, Leonilde, 1962-; Silveira, Clara, 1964- (Advances in business strategy and competitive advantage., 2021)
"This book is presents chapters describing research work in an organizational context in order to optimize the practices established in the most diverse domains of knowledge attending to the relation between ICT and sustainability in a post pandemic era"--